Public Trust in Government and Future Anxiety Among Generation Z: A Systematic Literature Review and an Integrated Conceptual Framework - Fharil Yosafat Panungkelan; Suhadianto Suhadianto; IGAA Noviekayati (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
governance challenges, including rapid digital transformation, political polarization, and macroeconomic uncertainty. Despite its growing importance, a significant theoretical gap persists regarding how institutional trust interacts with the psychological well-being of young adults, specifically concerning the future anxiety experienced by Generation Z. This systematic literature review integrates fragmented, interdisciplinary evidence from public administration, political science, developmental psychology, and digital governance to address this disconnect. Adhering strictly to the PRISMA 2020 guidelines and the SPAR-4-SLR framework, this study synthesizes empirical and theoretical evidence published between January 2021 and June 2026 to explore how digital governance structures and institutional trust shape the future orientation of young citizens. The thematic synthesis reveals a distinct "double-edged sword" effect within digital governance: while high-quality, transparent e-government services significantly strengthen internal political efficacy and institutional trust, algorithmically curated media environments often catalyze political alienation and institutional skepticism. Crucially, the findings demonstrate that political trust functions as a vital cognitive and emotional buffer, providing psychological resources that mitigate economic, environmental, and career-related future anxiety. By integrating these macro-level and micro-level dynamics, this study constructs an "Institutional–Psychological Nexus Framework" that explains how government stability, empathetic communication, and formal social support systems mediate psychological resilience among Generation Z. Ultimately, this research underscores that contemporary public institutions must evolve beyond mere administrative efficiency, prioritizing transparent, outcome-oriented digital engagement to alleviate youth anxieties and foster long-term democratic resilience.